1994
DOI: 10.1029/93wr03555
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved and colloidal contaminant transport in a partially clogged fracture

Abstract: A water‐saturated fracture, partially clogged with porous material coating the fracture surfaces, is considered. Fluid flow and contaminant transport in this fracture are significantly altered relative to an unclogged fracture. Analytical expressions are developed for the water velocities in the clogged and the unclogged regions in the fracture and the asymptotic longitudinal dispersion coefficient for the system. For highly adsorbing dissolved contaminants or large colloids, the slow diffusion within the poro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 41 publications
(7 reference statements)
0
10
0
2
Order By: Relevance
“…Beyond the engineering scope, the deposition process is also strongly relevant to environment and human health because it determines the transport and fate of colloids in ground water and other aquatic systems. Among these particles some are by themselves environmental contaminants (Kessler and Hunt ;Buddemeier and Hunt 1988) while some serve as vehicles to facilitate the transport of a variety of other contaminants that otherwise would be relatively immobile without the presence of the colloids (McCarthy and Zachara 1989;Corapcioglu and Jiang 1993;Grolimund, Borkovec et al 1996;Ryan and Elimelech 1996). Different types of environmentally relevant particles have been studied, including various minerals, Rajagopalan and Chu 1982;Puls and Powell 1992;Ryde, Kihira et al 1992) bacteria and viruses, (Logan, Hilbert et al 1993;Pieper, Ryan et al 1997;Ryan, Elimelech et al 1999;Redman, Walker et al 2004;Walker, Hill et al 2005) and engineered nanoparticles (Lecoanet, Bottero et al 2004;Brant, Lecoanet et al 2005;Saleh, Phenrat et al 2005;Chen and Elimelech 2006;Espinasse, Hotze et al 2007;Jaisi, Saleh et al 2008).…”
Section: Overview Of Deposition Studymentioning
confidence: 99%
“…Beyond the engineering scope, the deposition process is also strongly relevant to environment and human health because it determines the transport and fate of colloids in ground water and other aquatic systems. Among these particles some are by themselves environmental contaminants (Kessler and Hunt ;Buddemeier and Hunt 1988) while some serve as vehicles to facilitate the transport of a variety of other contaminants that otherwise would be relatively immobile without the presence of the colloids (McCarthy and Zachara 1989;Corapcioglu and Jiang 1993;Grolimund, Borkovec et al 1996;Ryan and Elimelech 1996). Different types of environmentally relevant particles have been studied, including various minerals, Rajagopalan and Chu 1982;Puls and Powell 1992;Ryde, Kihira et al 1992) bacteria and viruses, (Logan, Hilbert et al 1993;Pieper, Ryan et al 1997;Ryan, Elimelech et al 1999;Redman, Walker et al 2004;Walker, Hill et al 2005) and engineered nanoparticles (Lecoanet, Bottero et al 2004;Brant, Lecoanet et al 2005;Saleh, Phenrat et al 2005;Chen and Elimelech 2006;Espinasse, Hotze et al 2007;Jaisi, Saleh et al 2008).…”
Section: Overview Of Deposition Studymentioning
confidence: 99%
“…Kessler and Hunt [1994] suggested that when these materials clog the aperture, their porosity will dominate flow rates through the fractures. The roughness of fracture surfaces may also change over time as a result of mineral weathering [Anbeek 1992a, b; Anbeek et al, 1994; Murphy, 1993].…”
Section: Paper Number 1999wr900194mentioning
confidence: 99%
“…In a uniform-aperture fracture, the Taylor dispersion coefficient is only valid under fully developed flow conditions, that is when a fracture exceeds an entrance length defined as [25] (3)…”
Section: Methodsmentioning
confidence: 99%